An In Vitro Comparison of the Bond Strength of Composite to Superficial and Deep Dentin, Treated With Er:YAG Laser Irradiation or Acid-Etching - Alaghehmand, Homayoon; Nezhad Nasrollah, Fatemeh; Nokhbatolfoghahaei, Hanieh; Fekrazad, Reza (Journal of Lasers in Medical Sciences, 2016)
Introduction: The aim of this study was to compare the micro-shear bond strength of composite resin on superficial and deep dentin after conditioning with phosphoric acid and Erbium-Doped Yttrium Aluminum Garnet (Er:YAG) laser. Methods: Thirty human molars were selected, roots were removed and crowns were bisected to provide a total of 60 half-crowns. Specimens were ground to expose superficial and deep dentin. Samples were assigned to six groups: (1) AS (acid etching of superficial dentin); (2) AD (acid etching of deep dentin); (3) LS (Er:YAG laser irradiation on superficial dentin); (4) LD (Er:YAG laser irradiation on deep dentin); (5) LAS (Er:YAG laser irradiation on superficial dentin followed by acid etching); (6) LAD (Er:YAG laser irradiation on deep dentin followed by acid etching) The adhesive protocol was performed. Samples were thermocycled and micro-shear bond strength was tested to failure. The data were submitted to statistical analysis with one-way analysis of variance (ANOVA) and Tukey post hoc test. Results: The AS group, demonstrated the greatest amount of micro-shear bond strength. Statistical analysis showed a decrease in bond strength in laser-treated groups which was more significant for deep dentin. Conclusion: Preparation of dentin with laser did not improve bonding to superficial and deep dentin.